Visualization of the Scholarly Output on Evidence Based Librarianship: A Social Network Analysis - Vahed, Nafiseh; Gavgani, Vahideh Zarea; Jafarzadeh, Rashid; Tusi, Ziba; Erfanmanesh, Mohammadamin (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2018)
Objective – This paper aimed to analyze worldwide research on evidence based librarianship (EBL) using Social Network Analysis (SNA).Methods – This descriptive study has been conducted using scientometrics and a SNA approach. The researchers identified 523 publications on EBL, as indexed by Scopus and Web of Science with no date limitation. A range of software tools (Ravar PreMap, Netdraw, UCINet and VOSviewer) were utilized for data visualization and analysis.Results – Results of the study revealed that the United Kingdom (UK) and the United States (US) occupied the topmost positions regarding centrality measures, clearly indicating their important structural roles in EBL research. The network of EBL research in terms of the degree of connectedness showed low density in the co-authorship networks of both authors (0.013) and countries (0.214). Seven subject clusters were identified in the EBL research network, four of which related to health and medicine. The occurrence of the keywords related to these four subject clusters suggested that EBL research had a greater association with the setting of health and medicine than with traditional librarianship elements such as human resources or library collection management.Conclusion – This study provided a systematic understanding of topics, research, and researchers in EBL by visualizing the networks and may thus inform the development of future aspects of EBL research and education.